Human resources for health and decentralization policy in the Brazilian health system - Pierantoni Celia; Garcia Ana (BMC, 2011)
Abstract Background The Brazilian health reform process, following the establishment of the Unified Health System (SUS), has had a strong emphasis on decentralization, with a special focus on financing, management and inter-managerial agreements. Brazil is a federal country and the Ministry of Health (MoH), through the Secretary of Labour Management and Health Education, is responsible for establishing national policy guidelines for health labour management, and also for implementing strategies for the decentralization of management of labour and education in the federal states. This paper assesses whether the process of decentralizing human resources for health (HRH) management and organization to the level of the state and municipal health departments has involved investments in technical, political and financial resources at the national level. Methods The research methods used comprise a survey of HRH managers of states and major municipalities (including capitals) and focus groups with these HRH managers - all by geographic region. The results were obtained by combining survey and focus group data, and also through triangulation with the results of previous research. Results The results of this evaluation showed the evolution policy, previously restricted to the field of 'personnel administration', now expanded to a conceptual model for health labour management and education-- identifying progress, setbacks, critical issues and challenges for the consolidation of the decentralized model for HRH management. The results showed that 76.3% of the health departments have an HRH unit. It was observed that 63.2% have an HRH information system. However, in most health departments, the HRH unit uses only the payroll and administrative records as data sources. Concerning education in health, 67.6% of the HRH managers mentioned existing cooperation with educational and teaching institutions for training and/or specialization of health workers. Among them, specialization courses account for 61.4% and short courses for 56.1%. Conclusions Due to decentralization, the HRH area has been restructured and policies beyond traditional administrative activities have been developed. However, twenty years on from the establishment of the SUS, there remains a low level of institutionalization in the HRH area, despite recent efforts of the MoH.